Letter: addition of azathioprine to infliximab maintenance therapy in patients with anti‐drug antibodies and subclinical inflammation. Issue 4 (17th January 2018) - Primas, C.; Reinisch, S.; Novacek, G.
Abstract : Linked Content This article is linked to Ungar et al and Strik et al papers. To view these articles visithttps://doi.org/10.1111/apt.13862 andhttps://doi.org/10.1111/apt.13994 .